Inovasi Pembelajaran Pendidikan Agama Islam Menggunakan Media Audio Visual di SMP - Sodikin, Ahmad; Listiana, Lena; Taher Ichsan, Ahmad (Prodi Pendidikan Agama Islam, 2023)
Along with the development of science and technology that influences education, the utilization of science and technology (IPTEK) as a supporting tool for learning is one of the impacts of technological progress. This research aims to determine the innovation of Islamic religious education using audio-visual media and to identify the supporting and inhibiting factors of the innovation in the use of audio-visual media. The underlying issue is the innovation in the use of audio-visual media in Islamic religious education. This research is a descriptive study with a qualitative approach. The research methods include observation, interviews, and documentation. The results of the study can be summarized as follows: the innovation of Islamic religious education using audio-visual media is well-established and appropriate. The facilities and infrastructure of SMP Negeri 01 Belitang II Sumber Jaya are very adequate for using this media, creating a more interesting and enthusiastic learning environment for both students and teachers.